Differences in Spatial Understanding between Digital and Physical Models: A Comparative Experimental Design Study on "Presentation Techniques Studio Education - Karakoç, Erhan (My University, 2018)
In architectural education, "Presentation Techniques" is the first course that is obligatory for students who take the "Architectural Studio" course in order to improve their drawing skills. The purposed outcomes of the Presentation Techniques can be classified as two major principles such as: To have ideas and knowledge about two-dimensional and three-dimensional drawing techniques for appropriate manually prepared presentations, be able to identify, interpret, and use of two-dimensional and three-dimensional techniques to express the design correctly. In architectural education, instructors use digital or physical model for explaining form and its data. Students have many different approaches measuring and understanding the spatial properties of the given form. Presentation Techniques course have two different sessions. In the first session, the drawing methods are explained theoretically. In the second session, an application upon the theoretical part is completed. Students are experienced, assessed and analyzed spatial relationships of forms and subsequently constructed real models and digital models. One of the main purpose of the study is to identify how architecture students perceive forms in digital and physical platforms and how they sketch what they perceive. This study focuses on the differences in spatial understanding between physical and digital models. The methodology of the paper is structured on informing tire differences of spatial understanding of digital and physical models regarding Presentation Techniques course, literature review, experiments, expected outcomes, and results. The experiment has two phases. Students who are participated in the same theoretical class are randomly separated into 2 groups named A and B. Students will have the same duration for both of the experiments. Participants will have the same object, but for the first experiment, the participants of the group A will have a digital model of the object and group B will have the physical model of the object. After the submission of the drawings of the given objects there will be a survey analysis that will be applied to the students for examining spatial understanding of the digital and physical models in terms of the geometries and operations upon them. These drawings and surveys will be evaluated with a method that aimed to measure students' perception and understanding. The study achieves to find out which model is the better for teaching form and its data to students. The evaluations and results of the experiments will provide a proof for a better way of teaching spatial understanding to the instructor of the course. Future work should be done in different numbers of participants as perceived by professionals and non-professionals in the field of architectural education. Because of the drawing existing forms or models is the way of learning the representation of the 3D objects.
Keywords: Digital and Physical Models in Architecture; Architectural Perception